2013
DOI: 10.1073/pnas.1315278110
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial natural transformation by highly fragmented and damaged DNA

Abstract: DNA molecules are continuously released through decomposition of organic matter and are ubiquitous in most environments. Such DNA becomes fragmented and damaged (often <100 bp) and may persist in the environment for more than half a million years. Fragmented DNA is recognized as nutrient source for microbes, but not as potential substrate for bacterial evolution. Here, we show that fragmented DNA molecules (≥20 bp) that additionally may contain abasic sites, cross-links, or miscoding lesions are acquired by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 46 publications
4
142
1
2
Order By: Relevance
“…A single alignment with A. tumefaciens Ti-plasmid sequence of sufficient length and identity for HR (de Vries and Wackernagel, 2002;Monier et al, 2007;Hülter and Wackernagel, 2008;EFSA, 2009b;Overballe-Petersen et al, 2013) was identified, as expected. The alignment displayed 99.3 % identity over a 296 bp fragment of the Ti-plasmid containing the left border region used for transfer of the T-DNA.…”
supporting
confidence: 70%
“…A single alignment with A. tumefaciens Ti-plasmid sequence of sufficient length and identity for HR (de Vries and Wackernagel, 2002;Monier et al, 2007;Hülter and Wackernagel, 2008;EFSA, 2009b;Overballe-Petersen et al, 2013) was identified, as expected. The alignment displayed 99.3 % identity over a 296 bp fragment of the Ti-plasmid containing the left border region used for transfer of the T-DNA.…”
supporting
confidence: 70%
“…All the fitness values on group and single population levels are listed in Supplementary Table SI 5, respectively. In a control experiment ADP1200Com+ generated on average 2655 transformants per milliliter yielding a frequency of 2.7 × 10 -5 transformants per recipient (that is, natural transformation occurred below saturated DNA concentrations (Overballe-Petersen, Harms et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Active acquisition of random parts of the genetic material released by phylogenetically close organisms produces genetic polymorphism and functions as "localized sex" in reference to the function of sex in eukaryotic organisms (2). In addition, evidence suggests that genetic transformation can also occur with distantly related and even damaged DNA (3,4). Depending on the bacteria's biotope, the constant and random acquisition of genetic material could be as harmful as it is beneficial, and in most transformable species, natural transformation is a strictly regulated process (1,5).…”
mentioning
confidence: 99%